Improving the Living Standards of the Population through the Development of Family Entrepreneurship and Small Business in Uzbekistan - G. T. Samiyeva; B. I. Khaydarov (Research Parks Publishers, 2022)
The article discusses the role and importance of family business and entrepreneurship in poverty reduction, highlights the theoretical foundations of family business.